Penuaan Kulit dan Terapi yang Aman Bagi Geriatri: Artikel Review: Skin Aging and It’s Safe Management for Geriatrics: Review Article - Flora Ramona Sigit Prakoeswa; Winda Atika Sari (Jurnal Sains dan Kesehatan, 2022)
Geriatric have different skin characteristic compared with they who are in young age. There is a change in both intrinsic and extrinsic aging factors causing skin aging which is marked by skin wrinkles, loss of elasticity, and textural changes. The composition of collagen in geriatrics has decreased and there is an increase in matrix metalloproteinases resulted in skin aging. These conditions together with exposure to UVR, infection, and other risk factors cause various skin problems such as xerosis cutis, decubitus ulcers, dermatophytosis, and herpes zoster. Skin problems can be prevented by changing lifestyles, using some cosmetics, medications, and  having treatments. The prevention methods continues to grow and is still being researched to get optimal results and best suit skin conditions. Treatment of skin diseases in geriatrics should be carried out with caution considering the multimorbidity and immunosuppression that often occur in geriatrics. This article discusses skin differences in geriatrics, mechanisms of skin aging, common skin diseases, prevention, and safe treatment in geriatrics.